Answer:
-4
Step-by-step explanation:
- 4(m + 6) = - 8
(- 4)(m) + (- 4)(6) = - 8
- 4m - 24 = -8
- 4m = 16
m = - 4
66+10 would equal 77. 77 subtracted by 4 equals73 73 squared equals 5329. 5329 divided by 6 is 888.166667
Answer:
The coordinate (1, 0) is from a dilation using the scale factor of One-fifth.
Step-by-step explanation:
Answer:
Hypotenuse-Leg Theorem (HL)
Step-by-step explanation:
The HL theorem states that two right triangles are congruent if their hypotenuses are the same length and one leg is the same length. Since the diagram shows this, you can say these triangles through the HL theorem.